(untitled) (Research, Society and Development, 2020)
Spill and leakage stand out as rare and important adverse events in chemotherapy due to their risks. This study aims to determine the incidences and characterize these events, considering their determinants, patient profile and management according to the institutional protocol. This is a retrospective documentary, descriptive and transversal research, with a quantitative approach, carried out in an institution in Belém-Pará. Data collection covered the period from 2012 to 2019, subsidized by reading order and occurrence books, patient records and filling out a specific instrument. The data were structured in Microsoft Excel 2019 for descriptive and statistical analysis using the Chi-square test with p value <0.001 and the kolmogorov-smirnov test. 26 cases of spillage and 41 leakage were analyzed in 55 patients. The incidences of spillage and leakage were 0.08 and 0.13, respectively. Irritating antineoplastic drugs were more frequent in cases of spillage and vesicants had a higher rate in extravasation events, with emphasis on Paclitaxel. The follow-up to the institutional protocol was the majority, however, the measures were not recorded in detail in the medical records. The differential of this research was the joint analysis of the overflow and spill events, showing their concomitance. It is emphasized that the risks of these AEs must be monitored and duly notified, mainly by nursing professionals, aiming at the quality of health care, as well as the safety of professionals, patients and family members.